Histological and adhesiogenic characterization of the Zenapro Hybrid Hernia Repair Device. (2016) - Hodde, Jason P.; Suckow, Mark D.; Johnson, Chad; Rodenberg, Eric; Ritchie, Rae D.
Highlights: A hernia repair device made from polypropylene mesh and pig collagen is described. Adhesion formation was less extensive than controls. Tenacity of adhesions trended less than controls. Tissue remodeling and angiogenesis progressed over the span of the study. Abstract: Background: A major clinical problem relating to hernia repair is the formation of intra-abdominal, post-surgical adhesions when mesh products are used to reinforce the abdominal wall. To achieve better outcomes, more technologically-advanced products designed to achieve permanence of repair while eliminating serious complications such as adhesion formation are needed. This study was designed to assess the histological remodeling and adhesiogenic properties of the Zenapro™ Hybrid Hernia Repair Device as compared to uncoated and coated polypropylene. Materials and Methods: Zenapro™, Prolene ® and Ventralight ® ST Mesh were implanted to repair full-thickness abdominal wall defects in rabbits and rats and were allowed to survive for various lengths of time. Animals were euthanized, the implants were identified, and the extent and tenacity of adhesions were evaluated. Tissue samples were collected and evaluated for inflammation, integration of the mesh with the abdominal wall, and collagen deposition. Results: A significant difference was found in the extent of adhesions in the Prolene group as compared to the Zenapro group (p = 0.021) and the Ventralight ST group (p = 0.04) in the rat study. The tenacity of the adhesions in the Prolene mesh group trended higher than in the other groups but failed to reach statistical significance. Histological evaluation demonstrated that collagen accumulation was greatest for the Zenapro implants as compared to either the Ventralight ST or Prolene samples. At the conclusion of 6-months in the rabbit model, the Zenapro sites showed signs of a thicker repair composed of more organized mature collagen than was seen in the Ventralight ST samples. Neither device was found to elicit any sort of detrimental inflammatory tissue reaction. Conclusion: A combination hernia device composed of a complete extracellular matrix with a synthetic mesh can result in enhanced tissue ingrowth and neovascularization while maintaining high tensile strength and mitigating adhesiogenic effects.